Acute Vascular Disruption by 5,6-Dimethylxanthenone-4-Acetic Acid in an Orthotopic Model of Human Head and Neck Cancer - Seshadri, Mukund (Neoplasia Press Inc., 2009)
The sustenance of most solid tumors including head and neck cancers (HNCs) is strongly dependent on the presence of a functioning vascular network. In this study, we examined the acute effects of a tumor vascular disrupting agent (VDA), 5,6-dimethylxanthenone-4-acetic acid (DMXAA; ASA404), in an orthotopic model of human HNC. Noninvasive magnetic resonance imaging (MRI) was used to monitor the vascular response of orthotopic FaDu xenografts to VDA therapy. Untreated tumors showed a marked but heterogeneous pattern of enhancement after contrast agent injection on serial T1-weighted (T1W) MR images. After VDA treatment, T2W and T1W MRI revealed evidence of hemorrhaging and lack of functioning vessels (enhancement) within the tumor. Quantitative estimates of relative vascular volume also showed a significant (P < .01) reduction in DMXAA-treated tumors 24 hours after therapy compared with untreated controls. Histology and immunostaining of untreated orthotopic FaDu tumors revealed poorly differentiated squamous cell carcinoma histology with distinctly visible CD31(+) endothelial cells. In sharp contrast, minimal CD31 staining with irregular endothelial fragments and faint outlines of blood vessels were seen in DMXAA-treated tumor sections. CD31 immunostaining and histology also highlighted the selectivity of vascular damage and tissue necrosis after VDA therapy with no evidence of toxicity observed in normal salivary gland, heart, liver, and skeletal muscle tissues. Together, our results demonstrate a potent and selective vascular disruptive activity of DMXAA in an orthotopic HNC model. Further evaluation into its antitumor effects alone and in combination with other agents is warranted.